ADOPSI PENGGUNAAN APLIKASI MOBILE FOOD ORDERING DENGAN PENDEKATAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 - Widanengsih, Euis; Kurniadi, Win; Destiana, Henny (Journal of Industrial Engineering & Management Research, 2022)
The COVID-19 pandemic has changed the social order of human life, public health, and also business operations. With the number of social restrictions that have occurred, changing the pattern of food shopping in the community, the home-based food business has become the consumer's main choice in buying healthy food in the midst of the COVID-19 Pandemic. Consumers tend to prefer ordering healthy food and ordering food online by utilizing Mobile Food Ordering Applications. The purpose of this study was to measure the behavior of users of the Mobile Food Ordering application using the UTAUT 2 model, the UTAUT model which has been developed with the addition of independent variables. The data used in this study is primary data. Primary data is data obtained directly in the field. The data collection technique in this research is a survey. The sampling method used the purposive sampling method with the criteria for users of the Mobile Food Ordering application, namely GoFood, GrabFood and ShoppeFood in the last month. A survey of 100 respondents was conducted during November 2021. The collected data was processed using the SEM method with the Partial Least Square (PLS) approach with SmartPLS 3.0 software. The results of this study indicate that Performance Expectancy (PE) has no significant effect on Behavioral Intentions (BI). Effort Expectance (EE) or business expectations of application use have a significant effect on Behavioral Intentions (BI). Social Influence (SI) or social influence has no significant effect on Behavioral Intentions (BI). Facilitating Condition (FC) is not significant to Behavioral Intentions (BI) and Use Behavior (UB). Hedonic Motivation (HM) is not significant to Behavioral Intentions (BI), Price Value (PV) or Cost Suitability is not significant to Behavioral Intentions (BI), Habit (HT) or consumer habits significantly affect Behavioral Intentions (BI) and Use Behavioral (UB) ), Behavioral Intentions (BI) have a significant effect on Behavioral Use (UB).